Primary renal fibrosarcoma: A rare case report and review of literature - Agarwal Kiran; Singh Smita; Pathania O (Wolters Kluwer Medknow Publications, 2008)
Primary renal fibrosarcoma is a rare tumor. We describe a case of primary renal fibrosarcoma in a 54-year-old male who presented with abdominal lump and intermittent hematuria.